Design and Application of a Simple Bottle Capping Tool for Catering SMEs: Desain dan Terapan Alat Bantu Penutup Botol Sederhana Untuk UMKM Katering - Gatut Rubiono; Gatot Soebiyakto; Syamsul Bahri (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Pawon Mburi Catering uses plastic bottles with screw caps for packaging beverage products. The process of installing the lid which must be rotated with a little pressure causes problems of fatigue and abrasions on the fingers. A tool is needed for this packaging process. The aim of this community service is to design and implement a simple bottle cap tool technology. The design of the tools is carried out according to the size of the bottle cap used. Bottle closing aids are made from easily available materials and easy to manufacture. The material for the tool frame was chosen to be wood. A pair of bolts with threaded groove is used to hold the bottle cap so that it does not shift when rotated by utilizing the ribbed grooves on the bottle cap. This equipment has been used in the production process of takjil orders at the Pawon Mburi UMKM. The implementation of this bottle cap tool make the process of installing bottle caps easier. Installation of the cap is lighter and the fingers are protected from fatigue and abrasions.